Metabolomic profiling of anaerobic and aerobic energy metabolic pathways in chronic obstructive pulmonary disease. Issue 14 (July 2021) - Xue, Mingshan; Zeng, Yifeng; Lin, Runpei; Qu, Hui-Qi; Zhang, Teng; Zhang, Xiaohua Douglas; Liang, Yueting; Zhen, Yingjie; Chen, Hao; Huang, Zhifeng; Hu, Haisheng; Zheng, Peiyan; et al.
While there is no cure for chronic obstructive pulmonary disease (COPD), its progressive nature and the formidable challenge to manage its symptoms warrant a more extensive study of the pathogenesis and related mechanisms. A new emphasis on COPD study is the change of energy metabolism. For the first time, this study investigated the anaerobic and aerobic energy metabolic pathways in COPD using the metabolomic approach. Metabolomic analysis was used to investigate energy metabolites in 140 COPD patients. The significance of energy metabolism in COPD was comprehensively explored by the Global Initiative for Chronic Obstructive Lung Disease–GOLD grading, acute exacerbation vs. stable phase (either clinical stability or four-week stable phase), age group, smoking index, lung function, and COPD Assessment Test (CAT) score. Through comprehensive evaluation, we found that COPD patients have a significant imbalance in the aerobic and anaerobic energy metabolisms in resting state, and a high tendency of anaerobic energy supply mechanism that correlates positively with disease progression. This study highlighted the significance of anaerobic and low-efficiency energy supply pathways in lung injury and linked it to the energy-inflammation-lung ventilatory function and the motion limitation mechanism in COPD patients, which implies a novel therapeutic direction for this devastating disease.